Ga‐Doped Intermetallic Pd3Pb Nanocubes as a Highly Efficient and Durable Oxygen Reduction Reaction Electrocatalyst. Issue 16 (23rd April 2021) - Shen, Rong; Wu, Xingqiao; Li, Xiao; Huang, Jingbo; Luo, Sai; Li, Junjie; Qian, Ningkang; Ji, Liang; Yang, Deren; Zhang, Hui
Abstract: Pd‐based nanocrystals are a promising candidate as non‐Pt electrocatalysts for oxygen reduction reaction (ORR), but their performance still has large room to be improved. Here, we have successfully synthesized Ga‐doped Pd3 Pb nanocubes with different amounts of Ga by a simple one‐pot approach. When evaluated as electrocatalysts for ORR, the Ga‐doped Pd3 Pb nanocubes exhibited substantially enhanced catalytic properties in an alkaline media relative to the Pd3 Pb nanocubes and commercial Pt/C. Interestingly, the Ga‐doped Pd3 Pb nanocubes showed a volcano‐like relationship in ORR activity as a function of the amount of Ga with the 1.76 % Ga‐doped Pd3 Pb nanocubes (Pd3 Pb/Ga‐2 NC) being the best ORR electrocatalysts. Specifically, the Pd3 Pb/Ga‐2 NC/C exhibited the highest specific (7.57 mA cm −2 ) and mass activities (0.91 mA μgPd −1 ), which were 18.0 and 4.3 times higher than those of the commercial Pt/C. In addition, such Pd3 Pb/Ga‐2 NC/C displayed the higher durability with an increase of 14.2 % in mass activity after 20000 cycles relative to commercial Pt/C (74.9 % loss). This enhancement in both activity and durability can be attributed to the strong hybridization interactions and the formation of Pd shells on the surface by leaching of Pb. Abstract : Ga‐doped intermetallic Pd3 Pb nanocubes with different amounts of Ga were synthesized by a simple one‐pot approach. When evaluated as electrocatalysts for ORR, the Ga‐doped Pd3 Pb nanocubes exhibited substantially enhanced catalytic properties in an alkaline media relative to the Pd3 Pb nanocubes and commercial Pt/C. This enhancement in both activity and durability can be attributed to the strong hybridization interactions and the formation of Pd shells on the surface by leaching of Pb.